'I was there when she passed': older widowers' narratives of the death of their wife. Issue 6 (20th December 2012) - VAN DEN HOONAARD, DEBORAH K.; BENNETT, KATE MARY; EVANS, ELIZABETH
ABSTRACT: There is evidence that older widowed women provide narrative accounts of the events that led up to the deaths of their husbands. These accounts are qualitatively different from other parts of their interviews. This study examines interviews from older widowers and asks what features characterise their narrative accounts of their wife's death. The data show that men do speak of the death of their wife in a qualitatively different way than they do of other matters: women speak emotionally whilst men speak of their behaviour. Using Kirsi, Hervonen and Jylhä's typology of male care-givers, we find that their interviews are characterised by four types of speech: factual, agentic, familistic and destiny speech. In addition, we find two additional speech types related to blame – one related to medical negligence (a subset of destiny speech) and one to self-blame (a subset of familistic speech). We argue that the use of these patterns of speech allow men to preserve their masculine identities at a time when bereavement puts them under intense strain.